Revisão taxonômica das espécies neotropicais de Heterostylum Macquart, 1848 (Diptera, Bombyliidae, Bombyliinae) - Cunha, André Mallemont (2005)
The genus Hetrostylum Macquart contains medium size species (10 – 15 mm), and may be characterized for having a robust body covered by long pile. Contains 14 described species, of which nine are Neotropical and five are Nearctic. They are included among the Bombyliidae in the Homoeophthalmae division, differing from most genera in this division for presenting an indented hind margin of the eye. The revision of the Neotropical species is necessary because of their incomplete descriptions, the incomplete morphological knowledge, especially of the genitalia, and for the need of an identification's key for the species. The aim of this paper is to redescribe the genus Heterostylum Macquart and the known Neotropical species, present the main characters of external morphology, photos and illustrations of the genitalia of both genders and an identification key to the species. ln addition to the previously named species (H. bicolor (Loew), 1861, H. duocolor Painter & Painter, 1974, H. ferrugineum (Fabricius), 1805, H. haemorrhoicum (Loew), 1863, H. hirsutum (Thunberg), 1827, H. pallipes Bigot, 1892 and H. rufum (Olivier), 1789), two new ones were added, H. evenhuisi Cunha & Lamas, 2005 and H. maculipennis Cunha & Lamas, 2005. The studied material belongs to the collections of Museu Nacional, Rio de Janeiro; Museu de Zoologia da Universidade de São Paulo; Museu Paraense Emílio Goeldi; Universidade Federal do Paraná and to The Natural History Museum, London. The identification key was elaborated with the material studied in this paper, the original descriptions of H. duocolor (Painter & Painter, 1974) and H. bicolor (Loew, 1861) and the redescriptions of the neartic species recently published.